2009
DOI: 10.1292/jvms.71.885
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Paramylon, a .BETA.-1,3-D-Glucan Isolated from Euglena gracilis Z, on Acute Liver Injury Induced by Carbon Tetrachloride in Rats

Abstract: ABSTRACT. Paramylon is a -(1-3)-D-glucan isolated from Euglena gracilis Z. This study was designed to evaluate the protective effects of paramylon on liver injury induced by carbon tetrachloride (CCl 4 ) in rats. Wistar stain male rats were orally administered paramylon (500, 1,000 and 2,000 mg/kg body weight) before treatment with a single intraperitoneal dose of 50% CCl 4 (2 ml/kg body weight). The rats were sacrificed 24 hr later, and blood samples were collected for assay of serum biochemical parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 39 publications
(34 reference statements)
2
51
2
Order By: Relevance
“…Native paramylon shows cytokine-related immunopotentiating activity [18] and a hepatoprotective effect via antioxidative activities [32]. Sulfated derivatives of paramylon and N, N-dimethylaminoethyl paramylon exhibit both the anti-human immunodeficiency virus (HIV) and antimicrobial effects [16,27].…”
Section: Z Inhibits Development Of Atopic Dermatitis-like Skin Lesionmentioning
confidence: 99%
“…Native paramylon shows cytokine-related immunopotentiating activity [18] and a hepatoprotective effect via antioxidative activities [32]. Sulfated derivatives of paramylon and N, N-dimethylaminoethyl paramylon exhibit both the anti-human immunodeficiency virus (HIV) and antimicrobial effects [16,27].…”
Section: Z Inhibits Development Of Atopic Dermatitis-like Skin Lesionmentioning
confidence: 99%
“…It was established as a highly valuable source of protein with high methionine content, which is a characteristic of animal proteins (Kott and Wachs 1964;Hosotani and Kitaoka 1977;Kitaoka and Hosotani 1977). E. gracilis also contains all essential vitamins and nutritionally important polyunsaturated fatty acids, docosahexaenoic acid, and eicosapentaenoic acid in the cells (Stern et al 1960;Baker et al 1981) (euglena Co., Ltd., unpublished). In addition, recent studies have demonstrated the functionality of the Euglena-specific reserve polysaccharide, paramylon (Sugiyama et al 2009(Sugiyama et al , 2010Watanabe et al 2013), suggesting the commercial potential of E. gracilis.…”
Section: Introductionmentioning
confidence: 99%
“…Paramylon extracted from Euglena gracilis increases immune responses against infection in fish [12], exerts antioxidant protective action on acute hepatic injury in rats [13] and potentiates the resistance of shrimps against stress conditions during growing and handling [8]. It has also been suggested that highly nutritious proteins contained in Euglena species cells would strengthen the effect of paramylon; whereas antioxidant compounds would exert a direct protective action against oxidative stress [1].…”
Section: Introductionmentioning
confidence: 99%